THE APPLICATION EFFECT OF EMPTY PALM OIL BUNCH ORGANIC FERTILIZER RESIDUE AND NPK FERTILIZER IN CORN PLANTING ON SANDY SOIL - Salsabilla, Cindy Fidia; Afandi, Afandi; Wiharso, Didin (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
Conditions on sandy soil aggregate stability are generally classified as weak. This is because the sandy soil itself has a low organic matter content so that only a few plants can grow on the soil. Therefore, efforts must be made to improve the aggregate stability of the soil. The way that can be done is by adding organic fertilizer of empty palm bunches and also NPK fertilizer. This research was conducted from July 2023 to March 2024 in Marga Agung Village, South Lampung Regency. This study itself was carried out by applying a Randomized Block Design consisting of 7 treatments, namely A = Control; B = 1 NPK (350 kg/ha Urea, 100 kg/ha SP-36, 75 kg/ha KCl); C = ¾ NPK; D = ¾ NPK + 2 tons/ha Organic Fertilizer; E = ¾ NPK + 4 tons/ha Organic Fertilizer; F = ¾ NPK + 6 tons/ha Organic Fertilizer; G = 1 NPK + 8 tons/ha Organic Fertilizer. Then for the observation variables themselves, which include aggregate stability, c-organic, soil texture, and soil density. The results itself was analyzed using quantitative and qualitative methods by contrasting the analysis data which are contained determination class criteria. The results indicated that aggregate stability does not have a significant effect the residue of organic fertilizer of oil palm empty fruit bunches (TKKS) and NPK fertilizer. Treatment E = ¾ NPK + ½ Organic Fertilizer has the best aggregate stability compared to other treatments.